1985
DOI: 10.1063/1.96311
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and chemical stability of Schottky metallization on GaAs

Abstract: The high-temperature stability of Schottky barriers on GaAs has been correlated with the thermodynamic driving force for chemical reaction between the metallic contacts and the substrate. The chemical stability of a gate metallurgy can result in the stability of the electrical characteristics of the contact after high-temperature anneal. Since single element metal contacts on GaAs are chemically unstable, thermally stable Schottky barriers are not expected from these systems. Alternatively, most of the common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…It has been reported in the study on Co/n-GaAs Schottky diodes by Everaert et al [7] that contacts remained stable up to 300 C and deterioration started at temperatures above 300 C. As it can be seen from Fig. 2, the thermal stability of the CoCr alloy/n-GaAs contact maintained up to about 700 C. Lau et al [17] reported that the stability of electrical characteristics of a contact after high-temperature annealing was directly correlated to the chemical stability of the metallurgy.…”
Section: Resultsmentioning
confidence: 72%
“…It has been reported in the study on Co/n-GaAs Schottky diodes by Everaert et al [7] that contacts remained stable up to 300 C and deterioration started at temperatures above 300 C. As it can be seen from Fig. 2, the thermal stability of the CoCr alloy/n-GaAs contact maintained up to about 700 C. Lau et al [17] reported that the stability of electrical characteristics of a contact after high-temperature annealing was directly correlated to the chemical stability of the metallurgy.…”
Section: Resultsmentioning
confidence: 72%
“…27,28 This may have caused the Schottky contacts to deteriorate and turn into ohmic-like contacts after a high temperature RTA process. 29,30 The channel mobility (μ ch ), current on/off ratio (I ON /I OFF ), threshold voltage (V T ) and Schottky barrier height (φ B ) were also extracted from the I-V characteristics and plotted with cumulative annealing temperature for further investigation (Figures 2c and 2d). μ ch was calculated using…”
Section: Resultsmentioning
confidence: 99%
“…In the study on Ti/n-GaAs Schottky diode by Everaert et al [16], they reported that contacts remained stable up to 300 ¡C and deterioration started at 300 ¡C. Furthermore, this contact was predicted to the thermodynamically unstable by Lau et al [17]. In investigation by Jin et al [18] on e †ects of hydrogenation on Ti/n-GaAs Schottky barrier, they have found that the value in SBD U b diode without hydrogenation (0.76 eV) is larger than that in the SBD with hydrogenation (0.58 eV) at 300 ¡C.…”
Section: Resultsmentioning
confidence: 99%